2017
DOI: 10.1080/20018525.2017.1409060
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing pharmacological treatment in COPD: a comparison of 2005 and 2014

Abstract: Introduction: The aim was to investigate how the pattern of pharmacological treatment in Swedish patients with chronic obstructive pulmonary disease (COPD) has changed over a decade, and to identify factors associated with treatment. Methods: Data on patient characteristics and pharmacological treatment were collected using questionnaires from two separate cohorts of randomly selected primary and secondary care patients with a doctor’s diagnosis of COPD in central Sweden, in 2005 (n = 1111) and 2014 (n = 1329)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
(37 reference statements)
2
23
1
Order By: Relevance
“…The prevalence of discontinuation in our study was similar to that observed in previous publications, 40 – 42 in spite of different definitions of medication adherence/discontinuation being used. Haupt et al 41 saw that among patients who had received any inhaled medication, 24% received it only once during a 5-year period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of discontinuation in our study was similar to that observed in previous publications, 40 – 42 in spite of different definitions of medication adherence/discontinuation being used. Haupt et al 41 saw that among patients who had received any inhaled medication, 24% received it only once during a 5-year period.…”
Section: Discussionsupporting
confidence: 90%
“…However, short-acting pharmacological agents that may be prescribed for non-chronic conditions were included in that study. In another study, Sundh et al 40 found that 22% of COPD patients treated at hospitals lacked prescribed maintenance medication. Those results concerning discontinuation, low-dosage coverage or no maintenance treatment on discharge from hospital are in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of exacerbations as triggers of ICS prescription has been suggested in several other studies [14, 15, 30]. Many of these also identified associations between symptoms burden and treatment intensity [14, 23, 31]. In UK general practices, ICS use in GOLD A/B patients (in whom there is theoretically no indication of ICS according to most guidelines) appears associated with the level of airflow obstruction, concurrent asthma diagnosis and exacerbation rates as well as the region of the practice [30], suggesting that although markers of disease severity play a role, less objective or “scientific” factors are also involved.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is also real-world evidence that patients with COPD are more likely to initiate open-triple therapy following initiation with LAMA monotherapy, compared with LABA/ICS therapy 9 . It has been speculated that, at least in Sweden, the widespread use of triple therapy is due to the chronic characteristics of the disease, with a documented high proportion of persistent breathlessness in spite of maximum optimised treatment 10 . Other potential explanations may be increased availability of inhaled therapy in different devices and combinations, overtreatment due to heavy marketing from pharmaceutical companies, and increased awareness and implementation of GOLD ABCD recommendations.…”
Section: Introductionmentioning
confidence: 99%